2005
DOI: 10.1017/s0954579405050509
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment, attention networks, and potential precursors to borderline personality disorder

Abstract: Potential precursors to borderline personality disorder (BPD) were investigated in a sample of 185 maltreated and 175 nonmaltreated school-aged children attending a summer camp research program. Self-report, peer-report, and counselor-report measures were utilized to assess developmental constructs conceptualized to constitute vulnerability for later emerging BPD. These areas, including personality features, representational models of self, parent, and peers, interpersonal relationship difficulties with peers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 74 publications
4
133
0
7
Order By: Relevance
“…All of these may compromise cognitive and emotional regulation (Posner et al 2003). Indeed, individuals with BPD tend to display a disturbance in cognitive control processes (Posner et al 2003 ;Rogosch & Cicchetti, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these may compromise cognitive and emotional regulation (Posner et al 2003). Indeed, individuals with BPD tend to display a disturbance in cognitive control processes (Posner et al 2003 ;Rogosch & Cicchetti, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BPD assessments for children have been developed (Crick et al 2005 ;Rogosch & Cicchetti, 2005), and it appears that BPD-related features may be identified as early as 6 years of age, and remain relatively stable over time (Stepp et al 2010). Nevertheless, it has not been ascertained whether factors associated with BPD in adulthood are also associated with BPD symptoms during late childhood.…”
Section: Introductionmentioning
confidence: 99%
“…ex., émotionnel, verbal, physique et sexuel), la négligence (p. ex., des soins physiques de l'enfant, retrait émotionnel des parents, déni des besoins émotifs de l'enfant, manque de protection de la part des parents), les séparations multiples, le divorce des parents, ainsi que la criminalité, les traumatismes et les troubles des parents sont ciblés par la recherche sur l'étiologie du TPL (Battle et al, 2004 ;Bradley, Conklin et Westen, 2005 ;Johnson, Smailes, Cohen, Brown et Bernstein, 2000 ;Kernberg, 1990 ;Paris, 2000 ;Rogosch et Cicchetti, 2005).…”
Section: L'émergence Du Tpl Et Son éVolutionunclassified
“…In particular, it has be found that children who are the victims of sexual abuse show internalising and externalising difficulties, posttraumatic stress disorder symptoms, personality disorders and problems in interpersonal relations with peers [61,[106][107][108][109][110].…”
Section: Psychopathological Consequences Of Sexual Abusementioning
confidence: 99%